What policy makers need to know about COVID-19 protective immunity - Altmann, Daniel M; Douek, Daniel C; Boyton, Rosemary J (The Lancet (British edition), 2020)
The route to certainty on the degree and nature of the immunity required for protection will require evidence from formal proofs using approaches such as titrated transfers of antibodies and T lymphocytes to define protection in non-human primate models, as used, for example, in studies of Ebola virus.9 A study of survivors of SARS showed that about 90% had functional, virus-neutralising antibodies and around 50% had strong T-lymphocyte responses.10 These observations bolster confidence in a simple view that most survivors of severe COVID-19 would be expected to have protective antibodies. There are more than 100 candidate COVID-19 vaccines in development, with a handful in, or soon to be in, phase 1 trials to assess safety and immunogenicity.4 Candidate vaccines encompass diverse platforms that differ in the potency with which immunity is stimulated, the specific arsenal of immune mediators mobilised, the number of required boosts, durability of protection, and tractability of production and supply chains.3,4 Safety evaluation of candidate COVID-19 vaccines will need to be of the highest rigour. Some features of the immune response induced by infection, such as high concentrations of tumour necrosis factor and interleukin 6, which could be elicited by some candidate vaccines, have been identified as biomarkers of severe outcome.19 Researchers should be commended for decades of iterative efforts, bringing us to a point where there are many candidate vaccines in development against a novel virus first sequenced in January, 2020.